(Re-)reading Bede : the ecclesiastical history in context - Higham, N. J. (London, UK ; New York : Routledge, 2006)
"In (Re-)Reading Bede, N. J. Higham offers a fresh approach to how we should engage with this great work of history. He focuses particularly on Bede's purposes in writing it, its internal structure, the political and social context in which it was composed and the cultural values it betrays, remembering always that our own approach to Bede has been influenced to a very great extent by the various ways in which he has been both used, as a source, and commemorated, as man and saint, across the last 1300 years."--BOOK JACKET.
1. (Re-)reading Bede : an author and his audience -- 2. The Ecclesiastical history : Bede's purposes and ours -- 3. Structure, organisation and context -- 4. Message and discourse -- 5. Text and context : Bede, Ceolwulf and the Ecclesiastical history.
Formerly CIP.
Includes bibliographical references (p. [255]-272) and index.
Keywords: Bede -- the Venerable, Saint, -- 673-735.; Church history -- Middle Ages, 600-1500.; Civilization, Anglo-Saxon.; England -- Church history -- 449-1066.